THE LEVEL OF PATIENT FAMILY SATISFACTION IN THE EMERGENCY INSTALLATION (IGD): A DESCRIPTIVE STUDY - Azizah, Salma Iklil; Purwanto, Cucuk Rahmadi; Okviasanti, Fanni (Universitas Airlangga, 2025)
Introduction: The overcrowded Emergency Department (ED) conditions often make nurses feel overwhelmed when handling patients, causing family members to want their loved ones to be treated more quickly. However, in reality, the patient's condition may not be critical or an emergency. This leads the family to feel dissatisfied and unwilling to accept the services provided by nurses. This study aimed to determine the level of satisfaction among patient families in the ED of Dr. Soegiri Lamongan Regional Hospital. Methods: The research used a descriptive quantitative method with a convenience sampling technique. The sample consisted of 103 respondents who were family members of patients in the Emergency Department of Dr. Soegiri Lamongan Regional Hospital. The variable examined was family satisfaction, which was measured using the 20-item RATER questionnaire. Data analysis was conducted using univariate techniques and presented in frequency distribution tables. Results: The study show that the level of satisfaction among patient families in the ED of Dr. Soegiri Lamongan Regional Hospital was generally categorized as quite satisfied. Conclusions: Efforts undertaken by nurses and hospitals to improve and maintain patient and family satisfaction include routine room supervision and the implementation of nursing training activities to enhance the quality of nursing services and patient satisfaction at Dr. Soegiri Lamongan Regional Hospital. Institutions must be committed to fostering a high-quality service environment by providing staff with the necessary resources, facilities, and policies.